Prediction models constructed for Hashimoto’s thyroiditis risk based on clinical and laboratory factors - Li, Peng; Liu, Fang; Zhao, Minsu; Xu, Shaokai; Li, Ping; Cao, Jingang; Tian, Dongming; Tan, Yaopeng; Zheng, Lina; Cao, Xia; Pan, Yingxia; Tang, Hui; et al. (Frontiers in Endocrinology, 2022)
Background: Hashimoto's thyroiditis (HT) frequently occurs among autoimmune diseases and may synchronously appear with thyroid cancer. However, it is difficult to diagnose HT at an early stage just by clinical symptoms. Thus, it is urgent to integrate multiple clinical and laboratory factors for the early diagnosis and risk prediction of HT. Methods: We recruited 1303 participants, including 866 non-HT controls and 437 diagnosed HT patients. 44 HT patients synchronically had thyroid cancer. Firstly, we compared the differences in thyroid goiter degrees between controls and patients. Secondly, we collected 15 factors and analyzed their significant differences between controls and HT patients, including age, body mass index, gender, history of diabetes, degrees of thyroid goiter, UIC, 25-(OH)D, FT3, FT4, TSH, TAG, TC, FPG, low-density lipoprotein cholesterol and high-density lipoprotein cholesterol. Thirdly, logistic regression analysis demonstrated the risk factors for HT. For machine learning modeling of HT and thyroid cancer, we conducted establishment and evaluation of six models in training and test sets. Results: The degrees of thyroid goiter were significantly different among controls, HT patients without cancer (HT-C) and HT patients with thyroid cancer (HT+C). Most factors had significant difference between controls and patients. Logistic regression analysis confirmed diabetes, UIC, FT3 and TSH as important risk factors for HT. The AUC scores of XGBoost, LR, SVM and MLP models indicated appropriate predictive power for HT. The features were arranged by their importance, among which 25-(OH)D, FT4 and TSH were the top three high-ranking factors. Conclusions: We firstly analyzed comprehensive factors of HT patients. The proposed machine learning modeling combined with multiple factors are efficient for thyroid diagnosis. These discoveries will extensively promote precise diagnosis, personalized therapies and reduce unnecessary cost for thyroid diseases.